Application Of Customary Criminal Law In Deciding Crimes In The Marind Tribe Of Merauke - Budi Novianto; Ade Saptomo (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This research aims to analyze and document the application of customary criminal law in dealing with criminal acts in the Marind Tribe of Merauke. The Marind tribe of Merauke, as a community group that maintains traditional values and local wisdom, has a unique customary criminal law system that is deeply rooted in their traditions. The research results show that the customary criminal law system in this tribe plays an important role in maintaining social order and maintaining harmony among community members. The application of customary criminal law in the Marind Tribe of Merauke involves a process of deliberation, consensus, and the formation of collective decisions by traditional stakeholders. The decision includes traditional sanctions that reflect social norms and local wisdom values. Apart from that, this research also identifies the challenges and obstacles faced in implementing customary criminal law, especially in facing rapid changes in the social and economic environment. It is hoped that this research can contribute to understanding the dynamics of the application of customary criminal law in modern society. This research offers promise for criminal justice by providing findings that can help create a more effective and balanced approach to addressing criminal behavior. Combining traditional criminal law with a formal legal system can lead to a better and more efficient system for handling criminal activity.